2010
DOI: 10.1186/1471-2458-10-7
|View full text |Cite
|
Sign up to set email alerts
|

Do consumers' preferences for improved provision of malaria treatment services differ by their socio-economic status and geographic location? A study in southeast Nigeria

Abstract: BackgroundImprovement of utilization of malaria treatment services will depend on provision of treatment services that different population groups of consumers prefer and would want to use. Treatment of malaria in Nigeria is still problematic and this contributes to worsening burden of the disease in the country. Therefore this study explores the socio-economic and geographic differences in consumers' preferences for improved treatment of malaria in Southeast Nigeria and how the results can be used to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
2
11
1
Order By: Relevance
“…In accessing the various preferences of the patients, a study in Anambra state, Nigeria, (2010), showed that the choice of treatment and the most preferred source of provision of malaria treatment services for the respondents was based on the availability of such treatment which was public hospitals followed by training of mothers, treatment in Primary healthcare centers, traditional healers and patent medicine dealers were the least preferred strategies for improving malaria treatment. Some of the preferences differed by socio-economic status and by a lesser extent, the geographical location of the patient (Uguru, et al, 2010).…”
Section: Most Preferred Alternatives Base On Utility Functionmentioning
confidence: 99%
“…In accessing the various preferences of the patients, a study in Anambra state, Nigeria, (2010), showed that the choice of treatment and the most preferred source of provision of malaria treatment services for the respondents was based on the availability of such treatment which was public hospitals followed by training of mothers, treatment in Primary healthcare centers, traditional healers and patent medicine dealers were the least preferred strategies for improving malaria treatment. Some of the preferences differed by socio-economic status and by a lesser extent, the geographical location of the patient (Uguru, et al, 2010).…”
Section: Most Preferred Alternatives Base On Utility Functionmentioning
confidence: 99%
“…Changing climate conditions give rise to increased infectious disease such as malaria [3]. Water from rainfall can accumulate in places that become breeding sites for anopheles mosquitoes to lay and deposit their eggs, and larvae and pupae develop into adulthood.…”
Section: Climatementioning
confidence: 99%
“…The disease is the most common cause of outpatient visits in Nigeria [3]. Most rural Nigerian towns experience high malaria transmission, with an estimated 990,000 people dying from malaria in 1995; that is more than 2,700 deaths per day, or 2 deaths per minute.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations